THE EFFECT OF INTEREST IN LEARNING AND MASTERING VOCABULARY ABOUT THE ABILITY OF READING ENGLISH - Andri Kurniawan (JIPIS, 2020)
Abstract  The purpose of this study are to determine the effect of learning interest on students' English reading skills, to know the effect of vocabulary mastery on students' English reading skills, and to determine the effect of reading habits and mastery of vocabulary simultaneously on students' English reading skills. The research method used is survey. The population of this study were Private Vocational School students in Tangerang City in the academic year 2017/2018 totaling 1288 students and the samples were 200 students taken randomly. Data collection was carried out with questionnaires and test techniques. Data analysis used multiple regression analysis. The statistical test used is simultaneous test (F test) and partial test (t test). The results showed that: 1) There was a significant effect of learning interest and mastery of vocabulary together on students' English reading skills; 2) There is a significant influence of reading habits on English reading skills; and 3) There is a significant effect of vocabulary mastery on the ability to read English.